2009
DOI: 10.1007/s10967-009-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Depth profiles of potassium and its isotope ratio (40K/K) in several forest soils

Abstract: Depth profiles potassium and its isotope ratio ( 40 K/K) were investigated in several forest soils from different geological and climatic backgrounds. The ratio was found not to be constant (0.0117 %) but varied appreciably from 0.0085 to 0.0167 % among different soils.Possible factors affecting variability of 40 K/K values were considered by a multivariate factor analysis which suggested that aqueous parameters like humidity and pH might be a controlling factor in the surface soils. The amount (and probably c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
4
1
0
Order By: Relevance
“…137 Cs burial rate (cmy −1 ) ranged from 0.06 (P5) to 0.25 (P3) with the highest value at P3 under undisturbed beech stand in Kočevski Rog. Our previous investigation gave a relatively constant mean burial rate of 137 Cs of about 0.1 cm y −1 in different forest soils collected from various locations [2][3][4]. The findings in this study may also support our previous results.…”
Section: Environmental Radionuclides and Som In Surface Soilssupporting
confidence: 91%
See 1 more Smart Citation
“…137 Cs burial rate (cmy −1 ) ranged from 0.06 (P5) to 0.25 (P3) with the highest value at P3 under undisturbed beech stand in Kočevski Rog. Our previous investigation gave a relatively constant mean burial rate of 137 Cs of about 0.1 cm y −1 in different forest soils collected from various locations [2][3][4]. The findings in this study may also support our previous results.…”
Section: Environmental Radionuclides and Som In Surface Soilssupporting
confidence: 91%
“…The present authors obtained similar values of 137 Cs (and also 210 Pb) burial rate to those reported by Clouvas et al [9] in undisturbed forest soils from different places in Hokkaido, Japan, Germany, the Czech Republic and Peru [2][3][4]. Dynamic processes in soil were investigated using these nuclides of different origin and different chemical properties as radiotracers.…”
Section: Introductionsupporting
confidence: 88%
“…2b) -2 to 0.78 9 10 -2 %) appeared in the 216 surface portion (down to a depth of about 5 cm) compared 217 with those (0.86 9 10 -2 to 1.07 9 10 -2 %) in deeper part 218 (lower than 30 cm in depth) of the soil independent of the 219 location. Similar 40 K/K depth distribution profiles were 220 obtained in other locations of different geology [17].…”
supporting
confidence: 60%
“…The 321 result indicates that 40 K is enriched in the soils abundant in 322 SOM. Our previous investigation in Sapporo gave a similar 323 result [17]. As a possible evidence of changing 40 K/K ratios, 324 a plant species (Equisetum hyemale L.) and a litter sample 325 gave quite different 40 K/K values to those in the soil 326 (0.9 9 10 -2 to 1.3 9 10 -2 %) collected in November 2010 327 from semi-natural woods on the campus of Hokkaido Uni-328 versity in Sapporo, Japan.…”
supporting
confidence: 56%
See 1 more Smart Citation